Faktor-faktor Yang Mempengaruhi Return On Asset Bank Umum: Studi Kasus Pada PT Bank Mandiri (Persero) Tbk Periode 2011-2020 - Edy Safni Rosa; Siti Syafira Nurcahya; Wadudi Wibowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This research is meant to test the effect of Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), And Operational Efficiency Ratio (BOPO) Toward Return On Asset (ROA) Of PT. Bank Mandiri (Persero), Tbk. The population of this study is PT. Bank Mandiri (Persero), Tbk. The data is the secondary data which has been obtained from the banking annual financial statements which have been published at wbsite bank Mandiri in 2011-2020 periods. The sample collection technique has been carried out by using purposive sampling with 2 criteria and the samples are 40. The analysis method has been done by using multiple linear regressions analysis. The classic assumption test shows that normality test has been normally distributed, the heteroscedasticity test shows that heteroscedasticity does not occur, the autocorrelation test shows that autocorrelation does not occur, and the multicollinearity test shows that multicolinearity does not occur. The hypothesis test which has been done by using t test shows that NPL variable has negative and significant influence to the ROA, LDR variable has negative and significant influence to the ROA, and BOPO variable has negative and significant influence to the ROA. The result of this study indicate that the NPL, LDR, and BOPO variables have a simultaneous effect on ROA in the F test with a significant value f 0,00 < 0,05. Keywords: NPL, LDR, BOPO and ROA.